The influence of anticholinergic drug selection on the effectiveness of oximes against soman-induced supralethal poisoning in mice - Kassa, J (Acta medica (Hradec Kralove), 2001)
1. The influence of anticholinergic drugs (atropine, benactyzine, biperiden) on the efficacy of monopyridinium and bispyridinium oximes (HI-6, BI-6, obidoxime, pralidoxime, methoxime) on soman-induced supralethal poisoning was studied in mice. 2. While methoxime combined with benactyzine or biperiden seems to be more efficacious in the elimination of toxic effects of supralethal dose of soman than its combination with atropine, the efficacy of the other oximes studied against soman-induced toxic effects is not significantly influenced by the anticholinergic drug selection. 3. On the other hand, there are big differences in the effectiveness of oximes tested as to their ability to eliminate toxic effects of soman at supralethal doses. 4. The findings support the fact that the choice of acetylcholinesterase reactivator is more important than the anticholinergic drug selection for the effectiveness of antidotal mixture in the case of prophylactic administration of antidotes.
Keywords: soman; kombinovaná farmakoterapie; myši; oximy; chemické bojové látky; Male; Chemical Warfare Agents; Animals; Cholinergic Antagonists; Mice; Oximes; cholinergní antagonisté; mužské pohlaví; Drug Therapy, Combination; Soman; zvířata